2014
DOI: 10.1155/2014/757902
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Non-Newtonian Laminar Blood Flows through Arterial Double Stenoses

Abstract: The paper presents a numerical investigation of non-Newtonian modeling effects on unsteady periodic flows in a two-dimensional (2D) pipe with two idealized stenoses of 75% and 50% degrees, respectively. The governing Navier-Stokes equations have been modified using the Cartesian curvilinear coordinates to handle complex geometries. The investigation has been carried out to characterize four different non-Newtonian constitutive equations of blood, namely, the (i) Carreau, (ii) Cross, (iii) Modified Casson, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Appling to the first equation of system (7) operator ∇ and to the second operator t ∂ ∂ , they easily reduced to differential equation for perturbed pres-…”
Section: Dispersion Equation Of Capillary Waves and Her Decisionmentioning
confidence: 99%
“…Appling to the first equation of system (7) operator ∇ and to the second operator t ∂ ∂ , they easily reduced to differential equation for perturbed pres-…”
Section: Dispersion Equation Of Capillary Waves and Her Decisionmentioning
confidence: 99%
“…By comparison, non-Newtonian fluid viscosity changes depending on the shear rate. Literature demonstrates the relationship between blood viscosity and the shear rate for Newtonian and four different non-Newtonian models [23]. For our approach popular Carreau non-Newtonian model [23] is selected with features zero-shear plateau at low rates and a power-law region at high rates as demonstrated by the equation 4:…”
Section: J Biomed Eng Res 2016 | Vol 1: 102 Jscholar Publishersmentioning
confidence: 99%
“…e flow energy loss due to the presence of the stenoses, which is directly related to the pressure drop across them, increases with the number of stenoses but is not strongly dependent on the spacing between them. e authors of [11][12][13][14][15][16][17][18][19] have also investigated blood flow through multiple stenoses; however, these studies have not considered the mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that most CFD models of arterial hemodynamics make the simplifying assumptions of rigid walls and fully developed inlet velocities (cf. [13][14][15][16][17][18][19]). But the arteries are not rigid tubes.…”
Section: Introductionmentioning
confidence: 99%